Agroclimatic zoning of the state of Minas Gerais for the production of high quality soybean seeds - Pádua, Gilda Pizzolante De; França-neto, José De Barros; Rossi, Rubiana Falopa [UNESP]; Cândido, Humberto Gois (ABRATES - Associação Brasileira de Tecnologia de Sementes, 2014)
In Brasil, Minas Gerais is the sixth state in soybean production. Adverse climatic conditions such as short mini-droughts (veranicos), irregular rainfall distribution and especially high temperatures can compromise the proper development of the crop in that state, especially in relation to the production of high quality seeds. The aim of this study was to collect and analyze data in order to establish an agro-climatic zoning of the state of Minas Gerais for the production of high quality soybean seeds. These values were georeferenced in terms of the latitude and longitude coordinates and, with the use of a geographic information system, a thematic map was created, in which the best growing regions in Minas Gerais are represented. The definition of higher or lower climate risk areas was associated with the occurrence of average temperatures during the seed maturation phase, the most sensitive stage of growth. On the basis of the data obtained on temperature and altitude of different locations, and considering the normal growth period, it was possible to outline a map with three distinct areas: Favorable - average temperature < 23,5 ºC; moderately favorable - average temperature between 23,6 ºC and 24,9 ºC; Unfavorable - average temperature > 25,0 ºC.

Minas Gerais é o sexto estado em produção de soja no Brasil. Adversidades climáticas como veranicos, distribuição irregular das chuvas no decorrer do ano e principalmente temperaturas elevadas podem comprometer o bom desenvolvimento da cultura no Estado, principalmente no que se refere à produção de sementes de elevada qualidade. Diante disso, o objetivo desse estudo foi realizar um levantamento de dados com a finalidade de estabelecer um zoneamento agroclimático para a produção de sementes de soja de elevada qualidade física e fisiológica. Esses valores foram georeferenciados em função da latitude e longitude e, com o uso de um sistema de informações geográficas, foi confeccionado o mapa temático no qual estão representadas as melhores regiões para semeadura da cultura no Estado. A definição das regiões de maior ou menor risco climático foi associada à ocorrência de temperaturas médias na fase de maturação da soja, considerada a fase de máximo potencial fisiológico da semente, e da altitude dos municípios, tudo isso considerando a época normal de semeadura da cultura. Com base nos levantamentos realizados, estabeleceram-se três classes de regiões: Favorável – temperatura média < 23,5 ºC; Medianamente Favorável - temperatura média entre 23,6 ºC a 24,9 ºC; Pouco Favorável - temperatura média > 25,0 ºC.
Zoneamento agroclimático do estado de Minas Gerais para a produção de semente de soja de alta qualidade
Keywords: Glycine max (L.) Merrill; thematic map; production regions; temperature; Glycine max (L.) Merrill; mapa temático; regiões de produção; temperatura